Assessment of vegetation índices derived from UAV images for predicting biometric variables in bean during ripening stage - Quille Mamani, Javier Alvaro; Porras Jorge, Rossana; Saravia Navarro, David; Herrera, Jordán; Chávez Galarza, Julio César; Arbizu Berrocal, Carlos Irvin; Valqui Valqui, Lamberto (Universidad de Tarapacá, 2022)
7 páginas